LARAS BAHASA NASKAH PIDATO PEJABAT: LAPORAN KETERANGAN PERTANGGUNGJAWABAN GUBERNUR KEPADA DPRD KALIMANTAN BARAT TAHUN 2012 - Wahyu Damayanti (Balai Bahasa Sumatera Utara, 2019)
Language speech made Governor of West Kalimantan is the meeting place in this study. The use of speech language in fact governor is a public figure who may be a case for itself for its citizens. The purpose of research described pillihan use of words (diction) and spelling (capital letters and punctuation) Report on the Governor of West Kalimantan in 2012. Based on the purpose of this study the method used is descriptive method of analysis and interpretation techniques. Results of the research that is still contained inaccuracies such as cutting down the use of diction, foreign words, and reasoning. Which included the use of capital letters in the middle of a sentence that is not consistent, as well as the inclusion of punctuation colons and semicolons are not right.